2019
DOI: 10.3390/ijerph16203860
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Restorative Care and Factors Associated with Resident Outcomes in Long-Term Care Facilities in Taiwan

Abstract: This study aimed to analyze how restorative care is implemented in long-term care facilities and factors associated with resident outcomes in Taiwan. A one-group pre-test and post-test design was adopted in 24 long-term care facilities by collecting a sample of 310 participants at the baseline and 210 at six months. Participants were residents aged 65 or over, and were being constrained, used diapers, or were bedridden, or a combination of these. Their physical and mental functions were measured using Activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Two studies assessed restorative care, which emphasizes maintaining, restoring and optimizing residents' function, and one reported statistically significant results. The first study, assessing social support at baseline and 6 months after implementing a restorative care intervention, reported significant improvements in social support overall and for emotional and informational support domains 42 . The second study, testing the effect of a restorative care training and education program for supervisory and direct care staff, and comparing to usual care, suggested improvements in residents' social withdrawal, but the results were not statistically significant 43 …”
Section: Resultsmentioning
confidence: 99%
“…Two studies assessed restorative care, which emphasizes maintaining, restoring and optimizing residents' function, and one reported statistically significant results. The first study, assessing social support at baseline and 6 months after implementing a restorative care intervention, reported significant improvements in social support overall and for emotional and informational support domains 42 . The second study, testing the effect of a restorative care training and education program for supervisory and direct care staff, and comparing to usual care, suggested improvements in residents' social withdrawal, but the results were not statistically significant 43 …”
Section: Resultsmentioning
confidence: 99%
“…In nursing homes, the use of physical restraints for older adults is common in many countries (Bellenger et al, 2017 ; Foebel et al, 2016 ; Kor et al, 2018 ). The rate of physical restraint use in nursing homes is 18.8%–51.5% abroad (Abraham et al, 2019 ; Foebel et al, 2016 ; Huizing et al, 2009 ) and 62%–74% in Taiwan (Huang et al, 2014 ; Huang & Li, 2009 ; Lan et al, 2017 ). Compared to other countries, there is a tendency for a higher physical restraint rate in Taiwan's long‐term care facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Function‐focused care (FFC) is a philosophy of care that focuses on maximizing older adults' functioning (Galik, Resnick, Hammersla, & Brightwater, 2014). It is known as restorative care in the United States, Australia, Taiwan, and New Zealand; reablement in the United Kingdom, Ireland, and Denmark; and self‐supporting care in Japan (Wang, Chang, & Yeh, 2019). Instead of considering NHs as primarily residential areas for older adults with disabilities, restorative care is a more appropriate caring philosophy that aims to assess residents' basic functions to optimize their diverse functional abilities and improve physical activity (Baker, Gottschalk, Eng, Weber, & Tinetti, 2001; Resnick et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…FFC is a methodology designed to stimulate residents' involvement on a daily basis that has been shown to be safe and effective in improving functioning for activities of daily living (ADLs) (Ploeg & Leermakers, 2017). Therefore, FFC in NHs tends to focus on long‐term care, especially in relation to the quality of life (QOL) of older patients with frailty or disabilities (Henskens, Nauta, Scherder, Oosterveld, & Vrijkotte, 2017; Wang et al, 2019). However, according to a literature review regarding FFC in long‐term care, the psychological outcomes of FFC, such as depression and QOL, did not improve, nor did physical outcomes, such as gait, balance, and fall frequency, yet the authors suggested that maintaining functioning and/or reduced functional decline were considered positive findings in these studies (Resnick et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation